Peran Guru dan Mahasiswa KKN dalam Pengajaran Al-Quran di TPQ Miftahul Khairot Desa Bukit Peninjauan I - Ismail Ismail; Endang Lestari; Ardiman Zahri; Alfiyyah Agasi; Hendi M Ilham; Zhahwa Sherliana (Lembaga Pengembangan Kinerja Dosen, 2024)
This devotion discusses the Role of Teachers and KKN Students in Teaching the Quran at TPQ Miftahul Khairot, Desa Bukit Peninjauan I. KKN student devotion to help and teach the Quran to children. This activity not only focuses on knowledge transfer, but also involves various supporting aspects such as collaboration with TPQ teachers in order to improve the quality of Qur'an learning. This study aims to determine the role of teachers and KKN students in teaching the Qur'an at TPQ Miftahul Khairot, Desa Bukit Peninjauan I. This study uses a qualitative descriptive approach with observation, interview, and documentation methods. The results of this study show the role of teachers, namely as teachers, motivators, facilitators and supervisors. Meanwhile, the role of students as teachers, motivators and documentation